2021
DOI: 10.1007/978-3-030-67661-2_9
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Interactive Online Machine Learning Strategies

Abstract: In interactive machine learning, human users and learning algorithms work together in order to solve challenging learning problems, e.g. with limited or no annotated data or trust issues. As annotating data can be costly, it is important to minimize the amount of annotated data needed for training while still getting a high classification accuracy. This is done by attempting to select the most informative data instances for training, where the amount of instances is limited by a labelling budget. In an online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Olsson (2009) discussed AL for NLP tasks, while Schröder and Niekler (2020) discussed deep learning with AL. Our study also builds on Tegen et al (2020)'s use of simulation to study AL query strategies and MT assessment and teaching criteria. Lu and MacNamee (2020) reported on experiments where transformer-based representations performed consistently better than other text representations, taking advantage of the label information that arises in AL.…”
Section: Related Work and Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Olsson (2009) discussed AL for NLP tasks, while Schröder and Niekler (2020) discussed deep learning with AL. Our study also builds on Tegen et al (2020)'s use of simulation to study AL query strategies and MT assessment and teaching criteria. Lu and MacNamee (2020) reported on experiments where transformer-based representations performed consistently better than other text representations, taking advantage of the label information that arises in AL.…”
Section: Related Work and Backgroundmentioning
confidence: 99%
“…MT has been explored mostly in computing security, where the teacher is a hacker/advisor who selects training data to adjust the behavior of an adaptive, evolving learner (Alfeld et al, 2016(Alfeld et al, , 2017. Tegen et al (2020) reported that MT could greatly reduce the number of instances required, and even outperformed most AL strategies. These findings are compelling and motivate exploring MT's potential in NLP, which, however, has some distinct characteristics, including high-dimensional data impacted by scarcity.…”
Section: Related Work and Backgroundmentioning
confidence: 99%
See 3 more Smart Citations